A few rediscovered and challenging topics in polymer crystals and crystallization. Issue 4 (26th December 2018) - Yue, Kan; Liu, Gengxin; Feng, Xueyan; Li, Liangbin; Lotz, Bernard; Cheng, Stephen Z. D.
Abstract: This feature article discusses a few rediscovered and challenging topics in polymer crystals and crystallization. Among many research topics in this field, primary nucleation of polymers, twisted and curved polymer crystals, flow‐induced crystallization, and supramolecular crystals are selected and illustrated. This selection includes traditional topics with yet to be solved critical questions, and relatively new topics that still call for more developments. Specific attention is paid to the supramolecular crystallization of a new class of macromolecules termed "giant molecules, " which show unusual self‐assembly behaviors toward diverse hierarchical nanostructures. We believe that although being an old topic of long history, study on polymer crystallization will continue to flourish and will contribute to a more comprehensive understanding of self‐assembly in polymers. Abstract : Here we present a few rediscovered and challenging topics in polymer crystals and crystallization, including nucleation and curved crystals, flow‐induced crystallization, and supramolecular crystals of polymers. Altogether, we believe that further study on polymer crystallization will continue to flourish and contribute to a more comprehensive understanding of self‐assembly in polymers.